Digital Absence in the Age of AI: Examining an Extremely Marginalized Community Through the Lens of Inclusivity and Structural Violence - Budhathoki, Santosh (Journal of Advanced Academic Research, 2025)
Today, in the era of artificial intelligence (AI), the digital excess has become an essential right to education and inclusion. But it is a slinking persistent status of millions, like the Musahar, Chamar, Tatuwa, Dhobi, Dusad of The Terai plain of Nepal, the rate at which digital exclusion from access to information and technology is fucking difficult to integrate AI and social justice. Under me as a volunteer deputy director, the current research done for school children of the oppressed Dalit communities are the student studying for free tuitions organized by peace4dalits institute. Deputy Executive Director of the organization, who volunteer to speak-out. In a mixed-methods design, this study involves the collection of quantitative data from 200 students (20% of the 1000 in free tuition classes), as well as individual qualitative life history narrative interviews. Descriptively, the students’ families hardly hold any modern device, as only 2% have a mobile phone, none have a computer (0%), 2% own internet under the cellular model, which implies the use of a basic access to data. The qualitative findings reveal that two barriers account for this digital vacuum - poverty (families don’t have access to digital devices) and a lack of digital literacy (families do not have people to accompany/teach them). According to students, this disconnection means they are falling behind at school, lacking access to digital learning opportunities and have no idea what the changing digital world looks like. Yet even in community-operated tuition centers these obstacles still hinder their access to education and social inclusion. Finally, this article highlights that digital absence in such contexts is not merely a technological divide but a kind of structural violence. “Solving it demands comprehensive, affordable, community-based digital access programs ones that emphasize AI literacy and culturally sensitive digital literacy programmes that will leave no one behind in the AI era.